Development of a molecular method for detection and identification of Xanthomonas campestris pv. viticola - Trindade,Loiselene Carvalho da (2007)
In order to develop a molecular method for detection and identification of Xanthomonas campestris pv. viticola (Xcv) the causal agent of grapevine bacterial canker, primers were designed based on the partial sequence of the hrpB gene. Primer pairs Xcv1F/Xcv3R and RST2/Xcv3R, which amplified 243- and 340-bp fragments, respectively, were tested for specificity and sensitivity in detecting DNA from Xcv. Amplification was positive with DNA from 44 Xcv strains and with DNA from four strains of X. campestris pv. mangiferaeindicae and five strains of X. axonopodis pv. passiflorae, with both primer pairs. However, the enzymatic digestion of PCR products could differentiate Xcv strains from the others. None of the primer pairs amplified DNA from grapevine, from 20 strains of nonpathogenic bacteria from grape leaves and 10 strains from six representative genera of plant pathogenic bacteria. Sensitivity of primers Xcv1F/Xcv3R and RST2/Xcv3R was 10 pg and 1 pg of purified Xcv DNA, respectively. Detection limit of primers RST2/Xcv3R was 10(4) CFU/ml, but this limit could be lowered to 10² CFU/ml with a second round of amplification using the internal primer Xcv1F. Presence of Xcv in tissues of grapevine petioles previously inoculated with Xcv could not be detected by PCR using macerated extract added directly in the reaction. However, amplification was positive with the introduction of an agar plating step prior to PCR. Xcv could be detected in 1 µl of the plate wash and from a cell suspension obtained from a single colony. Bacterium identity was confirmed by RFLP analysis of the RST2/Xcv3R amplification products digested with Hae III.